Status of Indian One-horned Rhino, Rhinoceros unicornis Linn. 1758 in Dudhwa National Park, Uttar Pradesh, India - Tripathi, Dr. Arun Kumar (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2018)
Dudhwa National Park, located in the foothills of Himalayas in Uttar Pradesh (India), has become an ideal home to the Indian one-horned rhino, Rhinoceros unicornis Linn. 1758. The population in Dudhwa National Park was re-established in 1984-85, under Central Government Project, with rhinos being sourced from Assam (India) and Nepal. The population of rhino has grown in size manifolds over the last three decades. The rhino rehabilitation programme of Dudhwa can be deemed as one of the most successful initiatives of its kind in India. Present study, conducted in 2017 (January to December), provides vital information to strengthen the available data and to supplement the gaps in conservation and management plans for the Indian rhinos in Dudhwa National Park.